VD_FINDINFO HC / 2009 / 480 vom 8. Oktober 2009 - VD Tribunal cantonal (2009)
MODÉRATION, HONORAIRES, AVOCAT, DÉLAI DE RECOURS, DÉCOMPTESENS GÉNÉRAL | 207 al. 2 CC, 12 let. i LLCA, 45 al. 1 LPAv, 48 LPAv, 51 LPAv